Zinc / cobalt-based spinel oxide composite material catalyst as well as preparation method and application thereof

Through the preparation and application of zinc/cobalt-based spinel oxide composite catalyst, the problem of difficult degradation of p-nitrophenol is solved, and efficient reduction of p-nitrophenol and wastewater removal are achieved.

CN119500154AInactive Publication Date: 2025-02-25ZHEJIANG UNIV OF TECH +1

Patent Information

Application Number
CN202411630406.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively catalyze the reduction of p-nitrophenol, which makes it difficult to degrade in the environment and cause water pollution.

Method used

The ZnCo2O4 catalyst was prepared by hydrothermal and calcined processes using zinc/cobalt-based spinel oxide composite catalyst, and sodium borohydride was used as a reducing agent at room temperature to achieve efficient reduction of p-nitrophenol.

Benefits of technology

At room temperature, p-nitrophenol is completely reduced to p-aminophenol within 4 minutes, achieving the removal of harmful components in wastewater and reducing its toxicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500154A_ABST
    Figure CN119500154A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc / cobalt-based spinel oxide composite material catalyst as well as a preparation method and application thereof. The zinc / cobalt-based spinel oxide compound catalyst is prepared by taking zinc sulfate, cobalt nitrate and potassium oxalate as metal nodes and ligands through hydrothermal treatment and calcination. The ZnCo2O4 disclosed by the invention is applied to reduction of p-nitrophenol as a high-efficiency catalyst, and under the condition of room temperature, sodium borohydride is used as a reducing agent, and the efficiency of converting p-nitrophenol into p-aminophenol within 4 minutes can reach 100%. The zinc / cobalt-based spinel oxide composite material catalyst is synthesized by adopting a simple and environment-friendly method, the sodium p-borohydride has extremely high catalytic activity in reduction of p-nitrophenol, p-nitrophenol with relatively high toxicity can be reduced into p-aminophenol with relatively low toxicity, and the zinc / cobalt-based spinel oxide composite material catalyst has a potential application prospect in the fields of sewage treatment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heterogeneous catalysis, and specifically relates to a zinc / cobalt-based spinel oxide composite material catalyst, a preparation method thereof, and application of the catalyst in the reduction of p-nitrophenol. Background Art

[0002] p-Nitrophenol (4-NP) is a light yellow crystal, slightly soluble in water, easily soluble in organic solvents. When the solute is acidic, the light yellow gradually fades; when the acidity is between pH 3 and 4, the 4-NP solution is almost colorless; when the solute is alkaline, the color of the solution will deepen. p-Nitrophenol is a highly stable chemical raw material, widely used in industry, agriculture and medicine. It is widely used in the synthesis of acetaminophen, a substitute for aspirin, and in the production of pesticides such as parathion and methyl phosphine. p-Nitrophenol is difficult to degrade. In recent years, p-Nitrophenol has been detected many times in the ocean, river sediments, soil and other environments. 4-NP is one of the causes of widespread water pollution and is harmful to the health of marine animals. If inhaled by humans, it will damage the body's functional organs, increase the incidence of cancer and even cause systemic poisoning.

[0003] Spinel oxides (AB2O4) have attracted extensive attention in electrocatalysis due to their high elemental abundance, stable crystal structure, low cost and low environmental impact. In particular, spinel materials have been reported as effective catalysts for the thermocatalytic reduction of nitro compounds. As an important class of metal oxides, spinel oxides have attracted a lot of research interest due to their flexible ionic arrangement, multivalent structure and high electrical conductivity, which mainly include MFe2O4, MCo2O4 and MMn2O4.

[0004] In recent years, spinel oxides have attracted extensive attention due to their variable elemental composition, flexible structure and high thermal / chemical stability. In the spinel structure AB2O4, the A and B metal sites located at the tetrahedral and octahedral positions can be adjusted by various metal cations, which directly affect the redox performance and acidity of the catalyst. The position distribution of cations is an important factor affecting the activity of spinel oxides. Co3O4 spinel oxides have excellent Co 2+Redox properties and oxygen vacancies are widely used in different catalytic reactions. Substitution effect is one of the most commonly used strategies to modify spinel oxides to improve their catalytic performance. Zn is an indispensable trace element for the human body. At the same time, Zn is also widely used in industry. More importantly, the source of Zn is wide and the cost is low. Therefore, it is reasonable to use Zn to replace Co in Co3O4 spinel oxides. ZnCo2O4 is widely used in supercapacitors, electrolytes and electrocatalysis due to its excellent photochemical and electrochemical properties. However, there are no reports on the catalytic degradation of 4-NP by ZnCo2O4 spinel oxides. Its high catalytic activity and excellent redox stability make it a promising candidate for catalyzing the reduction of p-nitrophenol. Therefore, it is urgent to develop a preparation process for ZnCo2O4 spinel oxide composite catalysts. Summary of the invention

[0005] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a zinc / cobalt-based spinel oxide composite catalyst and a preparation method thereof and application in the reduction of p-nitrophenol.

[0006] The present invention aims to select a zinc / cobalt-based spinel oxide composite catalyst prepared by hydrothermal treatment and calcination of zinc sulfate (ZnSO4), cobalt nitrate (Co(NO3)2) and potassium oxalate (K2C2O4). The ZnCo2O4 of the present invention is used as a high-efficiency catalyst for the reduction of p-nitrophenol. Under room temperature conditions, with sodium borohydride as a reducing agent, the efficiency of converting p-nitrophenol into p-aminophenol can reach 100% within 4 minutes, thereby achieving the removal of harmful components in sewage and reducing its toxicity. The zinc / cobalt-based spinel oxide composite catalyst of the present invention is synthesized by a simple and environmentally friendly method, has extremely high catalytic activity for the reduction of p-nitrophenol by sodium borohydride, and has potential application prospects in the fields of sewage treatment.

[0007] The ZnCo2O4 in the present invention can achieve strict control of the zinc substitution site, making Zn 2+ In replacing Co 2+ At the same time, the sites are kept in the spinel structure of Co3O4 to form ZnCo2O4 with a normal spinel structure, ensuring that the excellent performance brought by the spinel structure is smoothly exerted in the process of reducing p-nitrophenol. When the ZnCo2O4 in the present invention is used for the reduction of p-nitrophenol in water, it can achieve rapid catalytic conversion for different concentration ratios of sodium borohydride and p-nitrophenol, and can still maintain a reaction conversion rate of 100% within 6 to 8 minutes.

[0008] The technical solution adopted by the present invention is as follows: On the one hand, the present invention provides a method for preparing a zinc / cobalt-based spinel oxide composite catalyst, the process is as follows: adding a potassium oxalate solution to a uniform dispersion of zinc sulfate and cobalt nitrate to produce a precursor solid product; by a one-step hydrothermal method, adding triethylamine to the mixture and placing it in an autoclave for hydrothermal reaction to obtain a zinc / cobalt-based spinel oxide composite material. The hydrothermal product is washed and dried and then calcined in a muffle furnace to obtain a final ZnCo2O4 catalyst.

[0009] Further, the specific process includes the following steps: 1) Add a certain proportion of ZnSO4·7H2O and Co(NO3)2·6H2O to deionized water and stir until completely dissolved; 2) Dissolve a certain amount of K2C2O4 in another beaker filled with deionized water. When all the added chemicals are completely dissolved, add the K2C2O4 solution dropwise to the beaker containing ZnSO4·7H2O and Co(NO3)2·6H2O while stirring continuously. A large amount of pink precipitate is gradually produced. The main components of the precipitate are pink precipitate CoC2O4 and white precipitate ZnC2O4. After adding the K2C2O4 solution, continue stirring for a while; 3) adding a certain amount of triethylamine to the mixed system obtained in step 2) to adjust the pore structure of the material, thereby increasing the specific surface area and pore volume of the material; 4) Transfer the mixture to a stainless steel autoclave lined with polytetrafluoroethylene, seal it and keep it in an oven for a period of time. During the hydrothermal reaction, the metal oxides and carbon dioxide produced by the hydrolysis of CoC2O4 and ZnC2O4 are rapidly converted into CoCO3 and ZnCO3 in the autoclave. Wait for it to cool naturally to room temperature, quickly filter the mixture in the autoclave, wash the solid product with distilled water and anhydrous ethanol respectively, and then dry it; 5) The composite material precursor obtained after drying is placed in a muffle furnace, and the product obtained after calcination is ZnCo2O4 catalyst. During the high-temperature calcination process, CoCO3 and ZnCO3 react at high temperature in an oxygen-rich atmosphere to generate ZnCo2O4 powder.

[0010] Furthermore, in step 1), the molar ratio of the added amounts of ZnSO4·7H2O and Co(NO3)2·6H2O is 1:(1.8-2).

[0011] Furthermore, the molar ratio of the amount of K2C2O4 added in step 2) to the amount of Co(NO3)2·6H2O added in step 1) is 1:(0.6-0.7).

[0012] Furthermore, the ratio of the amount of triethylamine added in step 3) to the amount of Co(NO3)2·6H2O added in step 1) is 1:(0.26-0.27).

[0013] Furthermore, in step 4), the oven temperature is set to 140-160° C. and the holding time in the oven is 12-15 h.

[0014] Furthermore, the calcination process in step 5) is: calcining at 400-450° C. for 3-5 h.

[0015] In a second aspect, the present invention proposes a zinc / cobalt-based spinel oxide composite catalyst prepared by the preparation method as described above, wherein Zn 2+ Replace Co 2+ And its site is maintained in the spinel structure of Co3O4, and a porous ZnCo2O4 material with a normal spinel structure is formed.

[0016] In the third aspect, the present invention also proposes the application of the above-mentioned zinc / cobalt-based spinel oxide composite material catalyst in the catalytic reduction of p-nitrophenol. Specifically, the zinc / cobalt-based spinel oxide composite material catalyst is dispersed in an aqueous solution and ultrasonically dispersed; p-nitrophenol and sodium borohydride are added, and p-nitrophenol is reduced to p-aminophenol under the catalysis of the zinc / cobalt-based spinel oxide composite material.

[0017] Furthermore, the reaction temperature is 25-50° C.; and the mass ratio of sodium borohydride to p-nitrophenol is 100:1 to 500:1.

[0018] Furthermore, the zinc / cobalt-based spinel oxide composite material has a high catalytic rate and can reduce p-nitrophenol to p-aminophenol within 4 minutes, and the degradation is complete.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1) The zinc / cobalt-based spinel oxide composite catalyst of the present invention is prepared by a simple one-step hydrothermal calcination method, which can ensure the integrity of the spinel structure and the excellent performance of the material, providing a new idea for the removal of p-nitrophenol in water and can be promoted and applied in the field of wastewater treatment.

[0020] 2) The present invention proposes for the first time that a zinc / cobalt-based spinel oxide composite catalyst be used for the removal of p-nitrophenol. Under the conditions of a temperature of 25°C, a pH of 9.5, a mass ratio of sodium borohydride to p-nitrophenol of 200:1, and a composite aqueous solution dosage of 50 microliters, p-nitrophenol can be reduced to p-aminophenol within 4 minutes, which has a significant advantage in reducing the toxicity of wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a transmission electron microscope image of the zinc / cobalt-based spinel oxide composite catalyst prepared by the present invention; Figure 2 is the degradation efficiency of p-nitrophenol under different p-nitrophenol concentration conditions; Figure 3 is the degradation efficiency of p-nitrophenol under different temperature conditions. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. Example 1

[0023] The method for preparing a zinc / cobalt-based spinel oxide composite material comprises the following steps: a. Add 1.4378 g of ZnSO4·7H2O and 2.9103 g of Co(NO3)2·6H2O to 60 mL of deionized water and stir with a magnetic stirrer until completely dissolved.

[0024] b. Dissolve 2.9477 g of K2C2O4 in another beaker with 60 mL of deionized water. When all the added chemicals are completely dissolved, add the K2C2O4 solution dropwise to the beaker with ZnSO4·7H2O and Co(NO3)2·6H2O while stirring continuously. A large amount of pink precipitate will gradually form. After adding the K2C2O4 solution, continue stirring for 10 min.

[0025] c. Add 5 mL of triethylamine to the mixed system obtained in step b.

[0026] d. Transfer the mixture to a 150 mL PTFE-lined stainless steel autoclave, seal it and keep it in a 140°C oven for 12 h. Allow it to cool naturally to room temperature and quickly filter the precursor. Wash the solid product with distilled water and anhydrous ethanol three times respectively and dry it at 80°C for 12 h.

[0027] e. Place the precursor in a muffle furnace and calcine it at 400°C for 3 h to obtain the ZnCo2O4 catalyst.

[0028] Depend on Figure 1It can be seen that the prepared zinc / cobalt-based spinel oxide composite catalyst presents a porous and flaky structure, the active substances are interlaced with each other, and there are obvious gaps between the active substances on the surfaces of different active substances. The advantages of this structure are: 1. Due to Zn 2+ and Co 2+ With the same size, Zn 2+ Can replace Co 2+ And keep its site in the spinel structure of Co3O4 and form ZnCo2O4 with normal spinel structure.

[0029] 2. By calcining the precursor, a large number of small molecules are flushed out to form abundant pores. The novel structure of the material is conducive to increasing the specific surface area of ​​the sample. Generally, samples with a large specific surface area can have more active centers and can show stronger catalytic performance. Example 2

[0030] Take 1 mg of the dried zinc / cobalt-based spinel oxide powder in Example 1, disperse it in 1 ml of deionized water, and ultrasonicate for 30 minutes to obtain a uniform dispersion. Take 0.1 ml of p-nitrophenol solution (0.13 mmol∙L -1 ), 1.9 mL of deionized water and 0.7 mL of sodium borohydride solution (0.1 mol∙L -1 ) in a cuvette, and finally add 50 microliters of the catalyst solution to react at a temperature of 25°C. While the reaction is in progress, the concentration of p-nitrophenol is tested by a UV spectrophotometer every 1 minute. The results are shown in the attached figure. Figure 2 shown. Example 3

[0031] In this Example 3, the preparation process of the zinc / cobalt-based spinel oxide composite material repeats steps a, b, c, d, and e in Example 1. The zinc / cobalt-based spinel oxide composite material prepared in Example 3 is applied to the catalytic reduction of p-nitrophenol. The experimental steps are the same as those in Example 2, except that the concentration of the p-nitrophenol solution in the reaction is 0.033 mmol∙L -1 The results are as attached Figure 2 shown. Example 4

[0032] In this Example 4, the preparation process of the zinc / cobalt-based spinel oxide composite material repeats steps a, b, c, d, and e in Example 1. The zinc / cobalt-based spinel oxide composite material prepared in Example 4 is applied to the catalytic reduction of p-nitrophenol. The experimental steps are the same as those in Example 2, except that the concentration of the p-nitrophenol solution in the reaction is 0.065 mmol∙L -1 The results are as attached Figure 2 shown. Example 5

[0033] In this Example 4, the preparation process of the zinc / cobalt-based spinel oxide composite material repeats steps a, b, c, d, and e in Example 1. The zinc / cobalt-based spinel oxide composite material prepared in Example 4 is applied to the catalytic reduction of p-nitrophenol. The experimental steps are the same as those in Example 2, except that the concentration of the p-nitrophenol solution in the reaction is 0.26 mmol∙L -1 The results are as attached Figure 2 shown.

[0034] from Figure 2 It can be seen that when sodium borohydride / p-aminophenol = 200:1, 4-NP concentration = 0.13 mmol × L -1 Under the reaction condition of 25 °C, the catalyst degradation effect showed different trends for different initial concentrations of p-nitrophenol. It can be seen from the figure that the concentration of p-aminophenol is 0.13 mmol∙L -1 When , p-nitrophenol can be completely reduced within 5 minutes. Example 6

[0035] In this Example 6, the preparation process of the zinc / cobalt-based spinel oxide composite material repeats steps a, b, c, d, and e in Example 1. The zinc / cobalt-based spinel oxide composite material prepared in Example 6 was applied to the catalytic reduction of p-nitrophenol. The experimental steps were the same as those in Example 2, except that the reaction temperature was 10°C. The results are shown in the attached figure. Figure 3 shown. Example 7

[0036] In this Example 7, the preparation process of the zinc / cobalt-based spinel oxide composite material repeats steps a, b, c, d, and e in Example 1. The zinc / cobalt-based spinel oxide composite material prepared in Example 7 was applied to the catalytic reduction of p-nitrophenol. The experimental steps were the same as those in Example 2, except that the reaction temperature was 40°C. The results are shown in the attached figure. Figure 3 shown. Example 8

[0037] In this Example 8, the preparation process of the zinc / cobalt-based spinel oxide composite material repeats steps a, b, c, d, and e in Example 1. The zinc / cobalt-based spinel oxide composite material prepared in Example 8 was applied to the catalytic reduction of p-nitrophenol. The experimental steps were the same as those in Example 2, except that the reaction temperature was 50°C. The results are shown in the attached figure. Figure 3 shown.

[0038] from Figure 3It can be seen that when sodium borohydride / p-aminophenol = 200:1, 4-NP concentration = 0.13 mmol × L -1 , the reaction temperature can be within the range of 25-50 ° C to reduce p-nitrophenol to p-aminophenol within 5 minutes. When applied to practical projects, the catalyst has little effect on temperature and can stably catalyze reduction. The amount of catalyst used is greatly reduced, and the effect is not attenuated. The substitution of zinc in the cobalt-based spinel oxide of the present invention reduces the cost of the catalyst, improves the catalytic activity, and promotes the reaction.

[0039] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.

Claims

1. A method for preparing a zinc / cobalt-based spinel oxide composite catalyst, characterized in that: The process is as follows: potassium oxalate solution is added dropwise to a uniform dispersion of zinc sulfate and cobalt nitrate to produce a precursor solid product; through a one-step hydrothermal method, triethylamine is added to the mixture and then placed in an autoclave for hydrothermal reaction to obtain a zinc / cobalt-based spinel oxide composite material; the hydrothermal product is washed and dried and then calcined in a muffle furnace to obtain the final ZnCo2O4 catalyst.

2. The method for preparing a zinc / cobalt-based spinel oxide composite catalyst according to claim 1, characterized in that: The specific process includes the following steps: 1) Add a certain proportion of ZnSO4·7H2O and Co(NO3)2·6H2O to deionized water and stir until completely dissolved; 2) Dissolve a certain amount of K2C2O4 in another beaker filled with deionized water. When all the added chemicals are completely dissolved, add the K2C2O4 solution dropwise into the beaker containing ZnSO4·7H2O and Co(NO3)2·6H2O while stirring continuously. A large amount of pink precipitate will gradually form. After adding the K2C2O4 solution, continue stirring for a while. 3) adding a certain amount of triethylamine to the mixed system obtained in step 2) to promote the formation of pore structure, thereby increasing the specific surface area and pore volume of the material; 4) Transfer the mixture to a stainless steel autoclave lined with polytetrafluoroethylene, seal it and keep it in an oven for a period of time, wait for it to cool naturally to room temperature, quickly filter the mixture in the autoclave, wash the solid product with distilled water and anhydrous ethanol respectively, and then dry it; 5) The dried composite material precursor is placed in a muffle furnace, and the product obtained after calcination is the ZnCo2O4 catalyst.

3. The method for preparing a zinc / cobalt-based spinel oxide composite catalyst according to claim 2, characterized in that: The amount of ZnSO4·7H2O and Co(NO3)2·6H2O added in step 1) is in a ratio of 1:(1.8-2); the amount of K2C2O4 added in step 2) is in a ratio of 1:(0.6-0.7) to the amount of Co(NO3)2·6H2O added in step 1).

4. The method for preparing a zinc / cobalt-based spinel oxide composite catalyst according to claim 2, characterized in that: The molar ratio of the amount of triethylamine added in step 3) to the amount of Co(NO3)2·6H2O added in step 1) is 1:(0.26-0.27).

5. The method for preparing a zinc / cobalt-based spinel oxide composite catalyst according to claim 2, characterized in that: In step 4), the oven temperature is set to 140-160° C. and the oven retention time is 12-15 h.

6. The method for preparing a zinc / cobalt-based spinel oxide composite catalyst according to claim 2, characterized in that: The calcination process in step 5) is: calcination at 400-450°C for 3-5 h.

7. A zinc / cobalt-based spinel oxide composite catalyst, prepared by the preparation method according to any one of claims 2 to 6, characterized in that: Zn 2+ Replace Co 2+ And its site is maintained in the spinel structure of Co3O4, and a porous ZnCo2O4 material with a normal spinel structure is formed.

8. Use of a zinc / cobalt-based spinel oxide composite catalyst as claimed in claim 7 in the catalytic reduction of p-nitrophenol, characterized in that: The zinc / cobalt-based spinel oxide composite catalyst is dispersed in an aqueous solution and ultrasonically dispersed; p-nitrophenol and sodium borohydride are added, and the p-nitrophenol is reduced to p-aminophenol under the catalysis of the zinc / cobalt-based spinel oxide composite.

9. Use of the zinc / cobalt-based spinel oxide composite catalyst according to claim 8 in the catalytic reduction of p-nitrophenol, characterized in that: The reaction temperature is 25-50° C.; the mass ratio of sodium borohydride to p-nitrophenol is 100:1 to 500:

1.

10. Use of the zinc / cobalt-based spinel oxide composite catalyst according to claim 8 in the catalytic reduction of p-nitrophenol, characterized in that: The zinc / cobalt-based spinel oxide composite material has a high catalytic rate and can reduce p-nitrophenol to p-aminophenol within 4 minutes, and the degradation is complete.

Citation Information

Patent Citations

  • Mn-doped g-C3N4 loaded porous ZnCo2O4 photocatalytic material and preparation method thereof

    CN111450871A

  • Composite spinel catalyst as well as preparation and application thereof in reverse water-gas shift reaction

    CN117138782A

Cited By

  • Method for activating and degrading pollutants in water by utilizing zinc-cobalt spinel catalyst piezoelectrically driven peroxymonosulfate

    CN122520229A